2009
DOI: 10.1107/s0108768109019880
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ion-migration paths in inorganic frameworks by means of tilings and Voronoi–Dirichlet partition: a comparison

Abstract: Two methods using Voronoi-Dirichlet polyhedra (Voronoi-Dirichlet partition) or tiles (tiling) based on partitioning space are compared to investigate cavities and channels in crystal structures. The tiling method was applied for the first time to study ion conductivity in 105 ternary, lithium-oxygen-containing compounds, Li(a)X(b)O(z), that were recently recognized as fast-ion conductors with the Voronoi-Dirichlet partition method. The two methods were found to be similar in predicting the occurrence of ionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 8 publications
2
20
0
1
Order By: Relevance
“…sets of migration paths of mobile cations within the framework) from crystallographic data, we used the program package TOPOS modified by Blatov et al (2006) for studying fast-ion conductors. An important difference compared with our previous study of the room-temperature KAlO 2 phase (Voronin et al, 2010) was that we used a novel algorithm based on the natural tiling concept (Anurova & Blatov, 2009) that is most applicable for compounds with rather simple framework topology. As opposed to the Voronoi-Dirichlet approach (Voronin et al, Table 1 Crystallographic data for KAlO 2 phases at different temperatures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…sets of migration paths of mobile cations within the framework) from crystallographic data, we used the program package TOPOS modified by Blatov et al (2006) for studying fast-ion conductors. An important difference compared with our previous study of the room-temperature KAlO 2 phase (Voronin et al, 2010) was that we used a novel algorithm based on the natural tiling concept (Anurova & Blatov, 2009) that is most applicable for compounds with rather simple framework topology. As opposed to the Voronoi-Dirichlet approach (Voronin et al, Table 1 Crystallographic data for KAlO 2 phases at different temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…Blatov et al (2007) showed that natural tiles and their faces (strong rings) correspond to minimal cages and windows of the framework, respectively. The net whose edges connect the centers of the natural tiles and pass through the tile faces is called dual net; it is the net that contains the migration map for fast-ion conductors (Anurova & Blatov, 2009). There is a one-to-one relation between topological elements of the framework and its dual net; in particular, nodes and edges of the dual net correspond to cages and windows of the framework.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a number of descriptors for inorganic materials are very similar to constitutional descriptors - essentially counts of various crystal parameters such as accessible surface areas and volumes [51, 52, 53]. Other descriptors characterize the periodic voids of porous materials via tessellation methods [54, 55]. …”
Section: A Categorization Of Descriptorsmentioning
confidence: 99%
“…Since the nodes and edges of the dual net correspond to cages and rings of the initial net, the dual net can be considered as a system of void centers and channel lines between them. Anurova and Blatov [53] showed that dual nets can be efficiently used to analyze the migration paths in fast-ion conductors, to predict the existence and dimensionality of conductivity. In MOFs, the self-dual nets are of special interest [12] because, being combined with the initial net, they form strongly catenated network arrays.…”
Section: ) Subnetsmentioning
confidence: 99%